Assessment of Differential Perceptions of Core Nursing Competencies between Nurse Managers and Nursing Graduates: A Cross-Sectional Study - Mahdi Tarabeih; Wasef Na'amnih (MDPI AG, 2023)
Background: The literature review on perceptions of nursing competencies shows a critical shortage of studies addressing this topic. Aim: To examine and compare perceptions of important nursing competencies of nursing graduates, and nurse managers. Methods: A cross-sectional study was conducted among 148 students, who were recent graduates of the nursing school with RN degrees and had completed advanced training lasting 3 months at the Sheba Academic School of Nursing and the Academic School of Tel Aviv-Yafo, and 183 nurse managers with at least one year of seniority in the position in hospitals and community clinics in Israel. The recruitment and data collection of the nurse managers lasted 12 months, from July 2021 to July 2022, and for nursing graduates, two months, from June 2022 to July 2022. An online questionnaire was constructed and validated by five professional and experienced individuals in the research domains for adequate content validity. The questionnaire consisted of 47 items in total. Domains included: (1) professionalism in research; (2) skills for direct treatment; (3) support and communication; (4) professional knowledge; (5) personal abilities; and (6) critical thinking and innovation. Results: Overall, 331 valid questionnaires were collected (85% response rate). The difference in the nurse's research professionalism index was found to be statistically significant with a higher rating given by nurse managers, p = 0.003. However, the difference in the direct treatment index of nurses was found to be statistically not significant, p = 0.610, between newly graduated nurses and nurse managers. The independent sample t-test indicated a significant difference with a higher rating among nurse managers in the nurse's support and communication index, p = 0.020; professional knowledge index, p < 0.001; personal abilities index, p < 0.001; and critical thinking index, p = 0.006, between newly graduated nurses and nurse managers. Conclusion: Nursing education programs aimed at training future nurses with core competences should include a curriculum designed to promote the acquisition of these six core competences leading to a congruence between the role expectations of nurse managers and those of newly graduated nurses.